Measles outbreaks - potential threat for health care professionals - A.C. Westgeest; D. de Mooij; C.Y. Eger; N.M. Delfos; M. van der Feltz; L.G. Visser; G.H. Groeneveld (Elsevier, 2020)
Summary: The ongoing spread of measles is a major concern for public health. Optimal vaccination coverage amongst health care professionals (HCP) is essential for individual protection. This is illustrated by our two cases of measles infection in HCP during the 2018 outbreak in Europe.We developed a questionnaire to assess protection against measles amongst HCP working in acute care of a tertiary hospital in The Netherlands. In total, 29% of these professionals were not protected against measles. During current worldwide measles outbreaks, it is paramount for employee health protection, patient protection and disease control to register and optimize employees' immunity.